Quality of diagnostic staging in patients with bladder cancer: A process‐outcomes link. Issue 3 (22nd October 2014) - Chamie, Karim; Ballon‐Landa, Eric; Bassett, Jeffrey C.; Daskivich, Timothy J.; Leventhal, Meryl; Deapen, Dennis; Litwin, Mark S.
Abstract : BACKGROUND: Muscle sampling is often used as a surrogate for staging quality in patients with bladder cancer. The association of staging quality at diagnosis and survival was examined among patients with bladder cancer. METHODS: The clinical records of all individuals within the Los Angeles Surveillance, Epidemiology, and End Results registry with an incident diagnosis of non–muscle‐invasive bladder cancer in 2004‐2005 were reviewed. Patient demographics, tumor characteristics, staging quality (presence of muscle in the specimen and mention of muscle in the pathology report), and vital status were recorded. With mixed‐effects and competing‐risks regression analyses, the association of patient and tumor characteristics with staging quality and cancer‐specific survival was quantified. RESULTS: The sample included 1865 patients, 335 urologists, and 27 pathologists. Muscle was reported to be present in 972 (52.1%), was reported to be absent in 564 (30.2%), and was not mentioned in 329 (17.7%) of the initial pathology reports. The presence of muscle did not differ according to the grade or depth of invasion. Mortality was associated with staging quality ( P  < .05). Among patients with high‐grade disease, the 5‐year cancer‐specific mortality rates were 7.6%, 12.1%, and 18.8% when muscle was present, absent, and not mentioned, respectively. CONCLUSIONS: The omission of muscle in the specimen or its mention in the pathology report in nearly half of all diagnostic resections was associated with increased mortality, particularly in patients with high‐grade disease. Because urologists cannot reliably discern between high‐ and low‐grade or Ta and T1 disease, it is contended that patients with bladder cancer should undergo adequate muscle sampling at the time of endoscopic resection. Cancer 2015;121:379–385. © 2014 American Cancer Society . Abstract : The medical records of 1865 patients with bladder cancer in Los Angeles County are reviewed, and suboptimal staging in nearly half of all diagnostic resections is found to be associated with increased mortality, particularly in patients with high‐grade disease.